Do Changes in Patellofemoral Joint Offset Lead to Adverse Outcomes in Total Knee Arthroplasty With Patellar Resurfacing? A Radiographic Review - Matz, Jacob; Howard, James L.; Morden, David J.; MacDonald, Steven J.; Teeter, Matthew G.; Lanting, Brent A. (The Journal of arthroplasty, 2017)
Patellofemoral joint biomechanics contribute to anterior knee pain, instability, and dysfunction following total knee arthroplasty (TKA). Information about specific factors leading to anterior knee pain and dysfunction is currently limited. Changes in patellofemoral joint offset (PFO) refers to a mismatch between the preoperative and postoperative anteroposterior geometry of the patellofemoral joint. It remains unclear whether these changes lead to adverse outcomes in TKA. A retrospective radiographic review of 970 knees pre-TKA and post-TKA was completed to correlate the radiographic and clinical outcomes of changing the PFO using a posterior-stabilized single knee design with patellar resurfacing. A total of 970 patients were reviewed. Postoperatively, the anterior femoral offset, anteroposterior femoral size, and anterior patellar offset were changed in 40%, 60%, and 71% of knees, respectively, compared to preoperative values. The Western Ontario and McMasters Osteoarthritis Index total score as well as subscale scores for pain and function were not significantly affected by an increase or decrease in PFO. Similarly, Knee Society Scores and range of motion were not significantly affected. Increased anterior patellar offset was, however, associated with increased postoperative patellar tilt. Postoperative patellar tilt was not correlated with adverse patient satisfaction scores or loss of range of motion. Changes in PFO (decreased, maintained, or increased) are common post-TKA and are not associated with a difference in clinical outcomes. Increases in anterior patellar offset led to increased patellar tilt, which was not associated with adverse patient satisfaction scores.